Hyper-crosslinked 4-amino-1, 8-naphthalimide Tröger's base containing pyridinium covalent organic polymer (COP) for discriminative fluorescent sensing of chemical explosives. Issue 9 (1st September 2020) - Delente, Jason M.; Umadevi, Deivasigamani; Byrne, Kevin; Schmitt, Wolfgang; Watson, Graeme W.; Gunnlaugsson, Thorfinnur; Shanmugaraju, Sankarasekaran
ABSTRACT: A new hyper-crosslinked 4-amino-1, 8-naphthalimide Tröger's base containing pyridinium covalent organic polymer, TBNap-COP, was synthesised and employed as a 'turn-off' fluorescent chemosensor for nitroaromatic explosives. TBNap-COP was synthesised in quantitative yield using a one-step nucleophilic substitution reaction between a dipyridyl scaffold (TBNap, bis-[N-(2-(pyridine-4-yl)ethyl)]-9, 18-methano-1, 8-naphthalimide-[b, f][1, 5]diazocine) and 1, 3, 5-tris(bromomethyl)benzene by heating in DMF for 3 days. The formation and phase-purity of TBNap-COP were fully characterised by using various spectroscopic and microscopy analyses. The suspension of TBNap-COP in water showed strong fluorescence emission characteristics owing to the 'push-pull' based ICT transition and it was used as a fluorescent sensor for discriminative detection of nitroaromatic explosives. TBNap-COP displayed selective fluorescence quenching responses for phenolic-nitroaromatics, with particularly high sensitivity for picric acid which is a powerful secondary chemical explosive and a harmful environmental pollutant widely used in the dye industries.